Rancangan Trucking Collaboration System - Sari Armiati; Muhammad Ibnu Choldun (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
Logistics company engaged in shipping services that have the activities of sending and receiving goods. Usually there is a Logistics Department division that is responsible for handling logistics business development, logistics project management, including vendor selection, making a bill recapitulation report from the vendor and sending bills to customers. In this study business process observations were carried out at PT XYZ which has a freight forwarding business. Business processes that occur at this time, the vendors that have been registered at PT XYZ will provide transportation services for shipping goods owned by PT XYZ partners according to dimensions of type, volume, size and weight of goods. It takes a long time for the Logistics Department to select a new vendor, the billing recapitulation by the billing admin is also made in different formats and there is no proper data storage in the Logistic Department. Based on these needs, we need a trucking collaboration system application design at PT XYZ company that has the functional ability to manage vendor selection data, manage bill recapitulation, and protect data. The design of this application will be a guideline in implementing software in the next research.